Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s13181-016-0583-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Use of Electronic Nicotine Delivery Systems (ENDS) to Vape Recreational Drugs by Club Patrons in South London

Abstract: Introduction Electronic nicotine delivery systems (ENDS, often called e-cigarettes) are nicotine delivery devices that heat nicotine into vapour that is inhaled, a process called 'vaping'. Use eclipsed nicotine-replacement therapy (NRT) in 2014 but ENDS role in smoking cessation remains controversial. Safety has not been proven and there have been reports to US poison centres regarding potential ENDS-related nicotine toxicity. A further concern is use of ENDS to vape recreational drugs, but there is limited da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Canada’s vaping restrictions were generally unenforced (Hammond et al, 2015) and after survey administration Canada implemented a new Vaping Products Act which relaxed many restrictions (Health Canada, 2018). Further, some youth also use vaping devices for marijuana or cannabis oil (Cassidy et al, 2018; Thurtle et al, 2017) and around the time of survey administration recreational marijuana use was legalized in Canada and several US states. Both the new Act and marijuana legalization were widely discussed around the time of this survey and may have influenced vaping norms; however, this is only speculation and would be difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…Canada’s vaping restrictions were generally unenforced (Hammond et al, 2015) and after survey administration Canada implemented a new Vaping Products Act which relaxed many restrictions (Health Canada, 2018). Further, some youth also use vaping devices for marijuana or cannabis oil (Cassidy et al, 2018; Thurtle et al, 2017) and around the time of survey administration recreational marijuana use was legalized in Canada and several US states. Both the new Act and marijuana legalization were widely discussed around the time of this survey and may have influenced vaping norms; however, this is only speculation and would be difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent animal study has revealed that a high IV ketamine dose caused the complete cessation of cortical EEG activity for several minutes, similarly to the 'K-hole' in humans [41]. Recently, online user fora, as well as research findings, also support vaping as a possible route of ketamine administration [42,43].…”
Section: Methods Of Ketamine Abusementioning
confidence: 98%
“…It can also be found in capsule or tablet form, sometimes with other psychoactive ingredients ( EMCDDA, 2002 ). The possibility of ketamine being ‘vaped’ has been aired in online user fora ( https://treato.com/Ketamine,Vaporizer/ ); there is some research evidence beginning to emerge supporting this as a route of administration ( Blundell et al, 2018 ; Thurtle et al, 2017 ).…”
Section: ‘State-of-the-art’ Reviewmentioning
confidence: 99%